The eye’s tactics during the visual search process - Rimkutė, E. (Psichologija, 1968)
The article deals with the issue of seeking and finding a given object (geometric shape) in a static exploration field on the basis of the eye movement cyclograms. The entire searching process is divided into two phases. The first stage of corresponds to the eye movement trajectory part after its start until the first time the eye catches the sought for figure. Then begins the second stage, which lasts until the final response. Four types of trajectories are identified by the consistency of exchanging fixation points in the first stage. Consistent systematic movements in circles occur most frequently. The first stage’s topography of fixation distribution demonstrated that the maximum period of fixation is focused on those figures in the search field that have elements similar to the searchable figure elements (basically they’re quite different shapes). The second phase is characterized by threefold eye tactics. In some cases, the research subject’s response coincides with the first searchable figure’s fixation. This latter figure is generally fixed for a considerably longer period than other figures in the field. Often even 2-3 sequential fixation points are distributed in the area they occupy. In other cases, eye movement trajectory does not end with fixation of the searchable figure, but rather continues to review a number of figures. The research subject’s response coincides with either another indifferent figure’s fixation or with a repeated glance returned to a searchable figure. Time spent recording searchable figures is considerably longer than the fixation time for other figures in the field. This suggests that while recording the sought after figure in the static exploration field with a glance other operations and activities that are different from the indifferent figures fixation action take place.